Remote interpreting in primary care settings: a feasibility trial in Germany - Jonas Fiedler; Susanne Pruskil; Christian Wiessner; Thomas Zimmermann; Martin Scherer (BMC, 2022)
Abstract Background Global migration trends have led to a more diverse population in health care services everywhere, which in turn has set off a paradigm shift away from medical paternalism toward more patient autonomy. Consequently, physicians need to provide a more precise patient-centred healthcare. Professional interpreting appears to play a crucial part in tackling the challenges of language barriers adequately. The aim of this study was to conduct process evaluation through the implementing of video remote interpreting (VR) and telephone remote interpreting (TR) within primary care facilities in the northern German metropolis of Hamburg. Methods We conducted a three-armed exploratory pilot trial, which compared VR to TR and to a control group (CG) in different primary care settings. We assessed feasibility of implementation, as well as the acceptance of interpreting tools among their users. In addition, we compared the quality of communication as perceived by patients and physicians, as well as the enabling of patient-centred medicine over all three study groups using quantitative questionnaires. Results 13 practices (7 GPs, 3 Gynaecologists, 3 Paediatricians) took part in this trial. 183 interpreting calls were documented, 178 physicians as well as 127 patients answered their respective questionnaires. The implementation of the VR- und TR-tools went smoothly and they were broadly accepted by their users. However, the tools were used significantly less often than we had anticipated. With regards to quantitative questionnaires, VR scored significantly better than the control group in terms of the perceived quality of communication by both, patients and physicians and enabled of patient-centred medicine. Conclusion Our main findings were the discrepancy between the assumed high demand of professional interpreting solutions on the one hand and the low willingness of practices to participate on the other. The rather low utilisation rates were also noteworthy. This discrepancy indicates a lack of awareness concerning the adverse effects of using informal or no interpreter in medical settings, which needs to be rectified. Due to the small sample size, all statistical results must be viewed with caution. However, our results show that remote interpreting represents a promising approach to tackling language barriers in primary care settings.